\[\boxed{\text{310\ (310).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (a + b) + \ *\ = 0\]
\[*\ = 0 - (a + b) = 0 - a - b =\]
\[= - a - b.\]
\[2)\ (a - b) + \ * = 0\]
\[*\ = 0 - (a - b) = 0 - a + b =\]
\[= - a + b.\]
\[3)\ ( - a - b) + \ * = 0\]
\[*\ = 0 - ( - a - b) = 0 + a + b =\]
\[= a + b.\]
\[\boxed{\text{310.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 2^{4} \cdot 2^{4} = 2^{4 + 4} = 2^{8}\]
\[2)\ 2^{4} + 2^{4} = = 2 \cdot 2^{4} = 2^{5}\]
\[3)\ 2^{n} \cdot 2^{n} = 2^{n + n} = 2^{2n}\]
\[4)\ 2^{n} + 2^{n} = 2^{n} \cdot 2 = 2^{n + 1}\]